Acid-base-induced fac → mer isomerization of luminescent iridium(iii) complexes. Issue 35 (22nd August 2022) - Yu. Gitlina, Anastasia; Fadaei-Tirani, Farzaneh; Ruggi, Albert; Plaice, Carolina; Severin, Kay
Abstract : From fac to mer and back: a clean, fast and simple procedure for the transformation of fac -Ir(C^N)3 complexes into the thermodynamically less stable mer isomers is described. The process enables the interconversion of luminophores with distinct photophysical properties. Abstract : Luminescent Ir(C^N)3 complexes (C^N = cyclometalated arylpyridine ligand) exist in the form of two stable isomers with distinct photophysical and electrochemical properties: fac and mer . Herein, we show that fac -Ir(C^N)3 complexes can be converted into the thermodynamically less stable mer forms by a consecutive reaction with first acid and then base. The chemically induced isomerization is fast, quantitative, and stereoselective, and it can be inversed by light. The new isomerization process opens the possibility to use highly luminescent Ir(C^N)3 complexes as molecular switches.